Kajian Perbaikan Tanah Dasar dan Proteksi Lereng pada Rencana Jalur Ganda Kereta Api Antara Giham-Martapura - Hidayat, Oktario Eko; Afriani, Lusmeilia; Siregar, Amril Ma'ruf (Universitas Lampung, 2020)
The train is a means of transportation favored by the community because the train is one of the modes of transportation that has special characteristics and advantages. Along with the development of infrastructure development in Lampung Province and South Sumatra Province, the planning and design of a building must be done carefully and well, one of them is by building a double track between Giham - Martapura, South Sumatra because the application of one track has many obstacles. It is hoped that the addition of the double track can make the train schedule more timely and can improve the quality of the trip. Based on the results of the Atterberg boundary test the soil originating from the undisturbed soil sample of the Giham-Martapura railroad gets an PI value <LL-30 (26.51% <27.95%), then the land based on the AASHTO system is classified into A -7-5 that is clay soil and as subgrade material has normal to poor evaluation. Keywords: railroad, land, double track, slope protection.